The Use and Abuse of Theodicy - Tilley, Terrence W. (Horizons, 1984)
The present essay distinguishes two ways to "settle" the problem of evil, "defense" and "theodicy," as practiced in contemporary Christian philosophical theology. It argues that Christian theology can defend Christian belief from the charge of inconsistency, but that when it attempts to explain why and how God permits or wills evil in his world, it stumbles over denying the reality of evil or the goodness of God. The essay concludes by arguing that the Christian theologian cannot and should not attempt to make Christianity plausible by constructing theodicies but should concentrate on other methods of demonstrating the plausibility of Christianity.